Application of visual management panel on an airplane assembly station. Issue 6 (9th July 2018) - Siaudzionis Filho, Felipe Alberto Bastos; Pontes, Heráclito Lopes Jaguaribe; Albertin, Marcos Ronaldo; de Lima, Raphael Luiz Maia; Moraes, Thais de Castro
Abstract : Purpose: The management of materials consists of an important analysis for industries as there are factors in several areas that should be considered. For this, it should take into account logistical factors, quality and production, because one piece delivered in a large lead time or outside the technical quality standards, imply delays in the project or rework. In this context, the importance of creating a control method of input and output of tools in an aviation industry in the city of Toulouse, France, was seen due to the amount of many incomplete arrivals or inappropriate material for use. The paper aims to discuss this issue. Design/methodology/approach: This study used a philosophy of lean manufacturing tools and visual management (VM). A VM panel with information documents of all tools used in an assembly station of a model airplane was applied. With all data collected to carry out the project, the panel was created with the most relevant information of each tool and applied to an assembly station. That done, the production supervisors, mechanical and electrical supervisors were trained in the operation. Despite a change of management, it was realized that all supported the change due to the ease of understanding of the method and a good VM. Findings: At the end of the work, materials management became more simplified, operators were more satisfied because of the non-occurrence of tools mistakes and the control time decreased from 120 to 15 minutes. Research limitations/implications: The application of this project has begun in an assembly station; however, it has been validated to be applied throughout the facility and its applications are being studied for other industries with different models. Practical implications: This project developed a visual panel for support visual communication of the airplane assembly line. Its usage eliminates tools lost, inefficiencies and decreases lost time with tools selection. Originality/value: This work proposes a way to simplify the management tools for assembly station plane using a VM panel based on the lean philosophy. The study was conducted at the Final Assembly Line of an aircraft model from a unit of an aircraft company.